Synergy analysis of tribocorrosion behaviour of aluminum alloy under different hydrostatic pressures - Zhengyi Li; Mengying Geng; Jiaxiang Wang; Lei Wen; Yibo Ai; Dongbai Sun (Journal of Materials Research and Technology)
Static corrosion, tribocorrosion tests, and potentiostat polarization tests were carried out on aluminum alloy 7075-T6 in 3.5 wt% NaCl solution. The influence of hydrostatic pressure on the tribocorrosion of the aluminum alloy in 3.5 wt% NaCl solution was studied, and the synergy relationship between its corrosion and wear was quantitatively analyzed. The results showed that the material loss of the aluminum alloy was not simply a superposition of corrosion and wear. The wear rate of corrosion-accelerated wear increased with the hydrostatic pressure, and when the hydrostatic pressure increased from 0.1 MPa to 30 MPa, the contribution of corrosion-accelerated wear increased by 15.43%. This research will help provide theoretical support for the selection of materials for deep-sea equipment.